KETAHANAN KELUARGA SEBAGAI BASIS PENDIDIKAN DI TENGAH PANDEMI COVID 19 - Dwi Yunianto (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2020)
This paper aims to describe the role of parents as educators to their children in the midst of the corona virus outbreak in the family environment. This paper uses a qualitative method with a descriptive analysis approach. The background of this paper is because many parents do not know their obligation to provide education to their children, especially in the family. Education in schools has apparently not been able to fully educate students, especially in the fields of religion and morals, this is evident by many students who do not understand religion, reading the Qur'an, are also increasingly widespread juvenile delinquency, ranging from fights, drugs and so forth. The purpose of education in the family is so that children are able to develop optimally both physically, spiritually, and intellectually. The role of parents in the education process is to use all means or methods such as examples, advice, story, or punishment. The role that is no less important is that parents provide educational material such as religious, social, physical, moral, and intellectual education.Keywords: Family, Base, Education